2013
DOI: 10.1186/1472-6882-13-171
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of advanced glycation end products by red grape skin extract and its antioxidant activity

Abstract: BackgroundThe objective of the present study was to determine the phytochemical content and the protective effect of red grape skin extract (RGSE) against fructose-mediated protein oxidation. In addition, RGSE was screened for its potential as an antioxidant using various in vitro models.MethodsAntioxidant activity was measured by 2,2-diphenyl-1-picrylhydrazyl (DPPH), hydroxyl radical scavenging activity, superoxide radical scavenging activity, trolox equivalent antioxidant capacity, ferric reducing antioxidan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 51 publications
2
65
0
Order By: Relevance
“…Recent data indicate that anthocyanin-enriched red grape skin extract demonstrates the ability to reduce the formation of AGEs, glycation-induced protein oxidation in BSA [35]. In the present study, we firstly investigated the effect of C3R on different types of monosaccharideinduced protein glycation.…”
Section: Experimental Groupsmentioning
confidence: 97%
“…Recent data indicate that anthocyanin-enriched red grape skin extract demonstrates the ability to reduce the formation of AGEs, glycation-induced protein oxidation in BSA [35]. In the present study, we firstly investigated the effect of C3R on different types of monosaccharideinduced protein glycation.…”
Section: Experimental Groupsmentioning
confidence: 97%
“…Several edible plants including berries (Wang et al 2011), red grape skin (Jariyapamornkoon et al 2013), pomelo (Caengprasath et al 2013), and Cyperus rotundus (Ardestani and Yazdanparast 2007), have shown antiglycation activities in BSA-fructose models. The major components of edible plants contain high phenolic compounds and flavonoids such as catechin, epicatechin, quercetin, rutin, kaempferol, p r o a n t h o c y a n i d i n s , h e s p e r i d i n , n e o h e s p e r i d i n dihydrochalcone, ellagic acid, gallic acid, and p-coumaric acid.…”
Section: Discussionmentioning
confidence: 99%
“…Eugenol, a phenylpropanoid from Ocimum Gratissimum, is an FDAapproved inhibitor of AGE that can be used for the management of diabetes and complications [25]. Compounds with AGE inhibiting property also act as natural ROS scavengers [26,27]. Polyol pathwayinduced AGE formation might be controlled by inhibiting the activity of ALR2.…”
Section: Discussionmentioning
confidence: 99%